Subject Headings for African American Materials - Brown, Lorene Byron (Libraries Unlimited, Inc, 1995)
This volume provides subject access to materials on all aspects of African American life and culture using the same format as the "Library of Congress Subject Headings" (LCSH). It lists approximately 5,000 subject headings that are interfaced and linked with LCSH. The list contains some of the problems that accompany the LCSH list because it is based, for the most part, on the practices of subject cataloging at the Library of Congress, but interlinking of headings with those of LCSH provides more specificity. The list is meant to be an accompaniment to, and not a substitute for, the LCSH. (Contains a list of 19 sources.) (SLD)